2021
DOI: 10.3389/feart.2020.591514
|View full text |Cite
|
Sign up to set email alerts
|

Microzoning Tsunami Hazard by Combining Flow Depths and Arrival Times

Abstract: Tsunami hazard is typically assessed from inundation flow depths estimated from one or many earthquake scenarios. However, information about the exact time when such inundation occurs is seldom considered, yet it is crucial for pedestrian evacuation planning. Here, we propose an approach to estimating tsunami hazard by combining tsunami flow depths and arrival times to produce a nine-level, qualitative hazard scale that is translated into a simple tsunami hazard map. To do this, one of the most populated regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Among these, 1730 was the only one to have inundation in Valparaíso, whereas 1922 and 2015 did cause inundation in Coquimbo. However, Zamora et al 68 found that events 9.0 are also capable of inundating the Valparaíso region, depending on the characteristics of the slip distribution. Hence, to account for source variability, these synthetic earthquakes were generated within this region using the Karhoenen-Loeve Expansion following Leveque et al 69 and Melgar et al 70 , considering a domain discretization of 10 x 10 km.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 1730 was the only one to have inundation in Valparaíso, whereas 1922 and 2015 did cause inundation in Coquimbo. However, Zamora et al 68 found that events 9.0 are also capable of inundating the Valparaíso region, depending on the characteristics of the slip distribution. Hence, to account for source variability, these synthetic earthquakes were generated within this region using the Karhoenen-Loeve Expansion following Leveque et al 69 and Melgar et al 70 , considering a domain discretization of 10 x 10 km.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical colored regions distinguish between the tsunami amplitude values used to categorize the hazard 21 . Horizontal coloring distinguish between very fast, fast and late arrivals, following 68 . Percentage values on the left indicate the cumulative fraction of events as a function of time.…”
Section: Methodsmentioning
confidence: 99%
“…To improve on the efficiency of synthetic catalogues, PTHAs often employ stratified-sampling by earthquake magnitude (e.g. De Risi & Goda, 2017;Williamson et al, 2020;Basili et al, 2021;Zamora et al, 2021). The Monte-Carlo accuracy of this approach is analysed below, and techniques are presented to estimate the errors both before and after high-resolution tsunami simulation.…”
Section: Sampling Approach and Statistical Properties Of The Monte-carlo Errormentioning
confidence: 99%
“…Both stratified and stratified/importance-sampling require fixing N (M w,b ) prior to sampling, and in practice uniform N (M w,b ) are often used (e.g. De Risi & Goda, 2017; Williamson et al, 2020;Zamora et al, 2021). However the computational effort is generally related to the total number of scenarios N tot :…”
Section: Improving the Efficiency: Non-uniform Sampling Of Magnitude-binsmentioning
confidence: 99%
See 1 more Smart Citation